A differential evolution approach to dimensionality reduction for classification needs - Martinović, Goran; Bajer, Dražen; Zorić, Bruno (Zielona Góra: Uniwersytet Zielonogórski)
The feature selection problem often occurs in pattern recognition and, more specifically, classification. Although these patterns could contain a large number of features, some of them could prove to be irrelevant, redundant or even detrimental to classification accuracy. Thus, it is important to remove these kinds of features, which in turn leads to problem dimensionality reduction and could eventually improve the classification accuracy.
Keywords: classification; differential evolution; feature subset selection; k-nearest neighbour algorithm; wrapper method